Willingness to Adopt Organic Farming Practices among Arable Crop Farmers in Oyo State, Nigeria - Omebere Okonta; Abiodun Ajala; Ayorinde Kolawole; Sunday Ogunjimi; Adewale Adejumo (Journal of Agricultural Extension, 2023)
Organic farming practices (OFP) are key components of sustainable agriculture. However, the adoption of OFP is not yet widespread. Therefore, this study examined the willingness to adopt OFP among arable crop farmers in Oyo State, Nigeria. A multi-stage and proportionate sampling technique was used to select 333 arable crop farmers with the aid of a structured questionnaire. Mean, percentages, Chi-square, and Pearson Product Moment Correlation ? 0.05 were used to analyse the results. Fifty percent (50%) of the respondents had high knowledge, and 46.1% had a moderately favourable perception of OFP. The majority (71.5%) were willing to adopt OFP. Inadequate credit facilities (=1.79) and lack of access to organic inputs ( =1.57) were major barriers to adopting OFP. Farm size (r = -0.114), household size (r = -0.180), farmer’s knowledge (r = 0.128), and perception of OFP (r = 0.122) were significantly related to farmers’ willingness to adopt OFP. Arable crop farmers were willing to adopt OFP. They should therefore be equipped with the requisite knowledge and skills through training programmes.